(untitled) (Bioresearch Communications, 2026)
Wild nectar-bearing plants play a vital role in supporting pollinators including butterflies by providing them with carbohydrate-rich nectar, thus contributing significantly to the stability of local ecosystems. The Jahangirnagar University (JU) campus functions as a semi-natural habitat, supporting a rich diversity of pollinators. This includes 60 butterfly species, which thrive with the support of 54 wild nectar-producing plant species from 30 distinct families. Among the plant families, the Asteraceae was the most represented, with 11 species, followed by Acanthaceae and Verbenaceae, each with 4 species. Other families included Fabaceae, Malvaceae, Solanaceae, Rubiaceae, Cleomaceae, Lamiaceae, Oxalidaceae and Tiliaceae each contributed two species, while the remainder families contributed one species each. In addition, floral traits such as corolla type and flower color were examined also to explore their relationship with butterfly. On the other hand, the campus was divided into 10 study sites, with the highest plant diversity (49 species) recorded near the Adjoining Swimming Pool (Site 8) and the lowest (28 species) near the Adjoining Statistics Department (Site 5). In the present study, 6 of the 54 selected plant species were processed for DNA barcoding using the matK gene, with the remaining 48 to be analyzed in the next phase. BLAST analysis showed 99.75–100% similarity with GenBank entries, validating the effectiveness of this gene for plant species identification. This molecular study is a stepping stone in refining DNA barcoding as a method for broader application to all 54 plant species. Nonetheless, this study not only provides insight into plant-butterfly associations but also advocates for the integration of molecular techniques in biodiversity assessments, enhancing our ability to accurately identify and monitor plant-pollinator relationships in natural habitats. Bioresearch Commu. 12(2): 2091-2101, 2026 (January)